Eficiência energértica de sistemas de abastecimento de água para diferentes pressões disponíveis nas entradas das edificações - Rocha, Nicolle de Belmont Sabino (2014)
Water and energy are two essential resources for society and have a strong interdependence. Among the major energy consumers, the sanitation sector stands out as one of the most demanding users. The electricity is in the top three most important companies cost items and, in many cases, is the second spending, second only to personnel expenses. Some studies estimate that power consumption to pump, treat and distribute water for urban populations is 2-3% of the total electricity consumed in the world. Faced with the search for more efficient alternatives, this paper aims to study the comparative energy efficiency of water supply systems for different pressures available at the entry points of buildings. Basically, the study compares the costs of implementation and operation of water distribution systems designed to supply buildings with facilities supplied directly and indirectly by the network. In the first system, the facilities have storage tanks for water from the distribution system, then it is pumped through its own system of impulse to a high reservoir, and the water then reaches the final consumer by gravity. The second system adopts a direct pumping system in buildings, eliminating the use of domestic reservoirs. The methodology adopted in this study used the optimized design of distribution networks through LENHSNET method, which determines the optimum design of the systems and facilities, and the EPANET simulation model. Later, the implementation and operation costs of the alternatives were calculated and evaluated. The results showed that, in economic terms, the system with direct pumping to the facilities is more expensive, because the system requires the pumps to run 24 hours a day.